2007
DOI: 10.1029/2007wr006021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of interfacial area per volume for drainage and imbibition

Abstract: [1] We investigate experimentally the functional relationship between capillary pressure, P c , wetting phase saturation, S w , and interfacial area per volume between the wetting and nonwetting phases, a wn , for drainage and imbibition processes in micromodels of twodimensional pore structures. Within the experimental and analysis error (around 10-15%), the resulting P c -S w -a wn surfaces were the same. This suggests that data obtained from either the drainage process or the imbibition process are sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 21 publications
(33 reference statements)
4
65
0
Order By: Relevance
“…This analysis corroborates previous experimental and computational studies (e.g., Reeves and Celia 1996;Held and Celia 2001;Cheng et al 2004;Chen et al 2007;Joekar-Niasar et al 2008, 2010bPorter et al 2009). It is presented here in order to establish equilibrium P c -S w -a nw surface needed for comparison to the corresponding non-equilibrium surface.…”
Section: On the Uniqueness Of Equilibrium P C -S W -A Nw Surfacessupporting
confidence: 81%
See 1 more Smart Citation
“…This analysis corroborates previous experimental and computational studies (e.g., Reeves and Celia 1996;Held and Celia 2001;Cheng et al 2004;Chen et al 2007;Joekar-Niasar et al 2008, 2010bPorter et al 2009). It is presented here in order to establish equilibrium P c -S w -a nw surface needed for comparison to the corresponding non-equilibrium surface.…”
Section: On the Uniqueness Of Equilibrium P C -S W -A Nw Surfacessupporting
confidence: 81%
“…In another study that compares experimental and pore-network model results for glass beads experiments, a similar conclusion was reached (Joekar-Niasar et al 2010b). These results indicated that inclusion of a nw leads to the removal or significant reduction of hysteresis in P c -S w relationship (see e.g., Reeves and Celia 1996;Held and Celia 2001;Cheng et al 2004;Chen et al 2007;Joekar-Niasar et al 2008;Porter et al 2009). All these studies have a common characteristics: the analyses were conducted under equilibrium conditions in which the capillary interfaces do not move in mostly granular media.…”
Section: List Of Symbolsmentioning
confidence: 85%
“…Two-dimensional micromodels with random pore distributions were used to demonstrate that the ambiguity of the hysteresis is lifted by the interfacial area per volume between the wetting and nonwetting phases (a wn ) [Chen et al, 2007;Pyrak-Nolte et al, 2008]. This previous work focused on thin 2D micromodels.…”
Section: Introductionmentioning
confidence: 99%
“…The total area of the microporous patterns was 600 × 600 mm 2 , and the sample thickness was approximately 1 or 2 mm. Interfacial length per area was investigated from optical images in previous work [Chen et al, 2007;Pyrak-Nolte et al, 2008], but it was difficult to measure the contact angles and the full 3D interface between the fluids. In this paper, we provide a method to directly visualize the 3D interfaces and 3D fluid distributions using laser scanning confocal microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Hassanizadeh and Gray showed (Hassanizadeh & Gray (1990;1993b)) that by formulating the conservation equations not only for the bulk phases, but additionally for interfaces, and by exploiting the residual entropy inequality, a relationship between capillary pressure, saturation, and specific interfacial areas (interfacial area per volume of REV) can be derived. This relationship has been determined in various experimental works (Brusseau et al (1997) Chen et al (2007) show that the relationship between capillary pressure, the specific fluid-fluid interfacial area, and saturation is the same for drainage and imbibition to within the measurement error. This allows for the conclusion that the inclusion of fluid-fluid interfacial area into the capillary pressure-saturation relationship makes hysteresis disappear or, at least, reduces it down to a very small value.…”
Section: Theoretical Backgroundmentioning
confidence: 99%